PELATIHAN GURU PAUD DALAM IMPLEMENTASI DONGENG INTERAKTIF ISLAMI BERBASIS MULTIMEDIA UNTUK OPTIMALISASI PERKEMBANGAN BAHASA ANAK - Andepi Daryana; Enih Hartiani; Siti Aminah; Nurul Fahimah; Marwah Triyati (Jurnal Pengabdian Indonesia (JPI), 2026)
The development of digital technology presents innovative opportunities in early childhood learning, particularly in stimulating language skills through interactive and meaningful approaches. Fairy tales as an educational medium have narrative power in enriching vocabulary and building children's expressive abilities, especially when combined with Islamic values ​​and multimedia support. This community service activity aims to improve the competence of early childhood education teachers in implementing interactive Islamic storytelling based on multimedia to optimize children's language development in Kutawaluya District. The method used was a participatory approach through the stages of needs assessment, workshops, media creation practice, classroom implementation assistance, and evaluative reflection with the teacher community. The results of the activity showed an increase in teacher capacity in designing and using digital media pedagogically, changes in learning interaction patterns to be more dialogic, and increased verbal participation of children in storytelling activities. In addition, a community of teacher practice was formed that collaboratively developed Islamic storytelling media as a sustainable innovation. The implications of this activity confirm that the integration of technology, Islamic values, and a participatory approach effectively encourages the transformation of early childhood learning practices. This model has the potential to be replicated in similar contexts to strengthen the quality of adaptive and character-building early childhood education.